Peran Valuasi Ekonomi Sumber Daya Alam Dalam Pembangunan Wilayah di Indonesia - Bhimo Rizky Samudro (EKO-REGIONAL, 2006)
Economic valuation of natural resources is important method in regional development. By this term, all potencies, characteristics, and economic value (benefit, cost, and profit) of natural resources should be known.  It can be also a fundamental concept to create regional rules and to make simple adjustment with The Act of National Natural Resources. The management of natural resources in regional area should match with regional potency and national vision of natural resources management. Finally, the country has to maintain the natural resources and also take care of its sustainability.  Keywords: Economic valuation, regional development